Arousal characteristics in patients with Parkinson's disease and isolated rapid eye movement sleep behavior disorder. Issue 12 (2nd July 2021) - Brink-Kjær, Andreas; Cesari, Matteo; Sixel-Döring, Friederike; Mollenhauer, Brit; Trenkwalder, Claudia; Mignot, Emmanuel; Sorensen, Helge B D; Jennum, Poul
Abstract: Study Objectives: Patients diagnosed with isolated rapid eye movement (REM) sleep behavior disorder (iRBD) and Parkinson's disease (PD) have altered sleep stability reflecting neurodegeneration in brainstem structures. We hypothesize that neurodegeneration alters the expression of cortical arousals in sleep. Methods: We analyzed polysomnography data recorded from 88 healthy controls (HC), 22 iRBD patients, 82 de novo PD patients without RBD, and 32 with RBD (PD + RBD). These patients were also investigated at a 2-year follow-up. Arousals were analyzed using a previously validated automatic system, which used a central electroencephalography lead, electrooculography, and chin electromyography. Multiple linear regression models were fitted to compare group differences at baseline and change to follow-up for arousal index (ArI), shifts in electroencephalographic signals associated with arousals, and arousal chin muscle tone. The regression models were adjusted for known covariates affecting the nature of arousal. Results: In comparison to HC, patients with iRBD and PD + RBD showed increased ArI during REM sleep and their arousals showed a significantly lower shift in α-band power at arousals and a higher muscle tone during arousals. In comparison to HC, the PD patients were characterized by a decreased ArI in non-REM (NREM) sleep at baseline. ArI during NREM sleep decreased further at the 2-year follow-up, although not significantly. Conclusions: Patients with PD and iRBD present with abnormal arousal characteristics as scored by an automated method. These abnormalities are likely to be caused by neurodegeneration of the reticular activation system due to alpha-synuclein aggregation.